2010
DOI: 10.1021/ol101909f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Inherently Chiral Calix[4]arenes: Stereocontrol through Ligand Choice

Abstract: Employing a chiral oxazoline as an ortholithiation directing group allows the synthesis of inherently chiral calix[4]arenes suitable for elaboration into planar chiral molecules. An important finding has been that the diastereoselectivity of the reaction can be tuned by the choice of additive. These results have bearing on the elucidation of the general mechanism of oxazoline-directed ortholithiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…These calix[4]arenes were then subjected to ortholithiation conditions varying the solvent, alkyllithium and ligand. The results are reported in Table 1 , which for the purposes of comparison, also includes data from our previously published work on the isopropyloxazoline calix[4]arenes 1a and 1b [ 27 28 ]. The conversion values and diastereomer ratios were determined either by NMR spectroscopy or HPLC traces.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These calix[4]arenes were then subjected to ortholithiation conditions varying the solvent, alkyllithium and ligand. The results are reported in Table 1 , which for the purposes of comparison, also includes data from our previously published work on the isopropyloxazoline calix[4]arenes 1a and 1b [ 27 28 ]. The conversion values and diastereomer ratios were determined either by NMR spectroscopy or HPLC traces.…”
Section: Resultsmentioning
confidence: 99%
“…Here the ratio of diastereomers was found to be opposite to those obtained when using the other alkyllithiums. Indeed diastereoselective reversals of this type have only rarely been observed in the literature [ 28 31 ] but importantly offer the advantage of accessing both inherently chiral antipodes after removal of the oxazoline. This avoids the need to resort to the more expensive oxazoline enantiomer derived from D- tert- leucine.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our own work in the area of meta-functionalised ICCs was influenced by Chen and Huang's attempta tu sing ac hirald irecting group. We howeverc hose to study the asymmetric ortholithiation of chiral oxazolines [51][52][53][54] and, mostr ecently,a chiral sulfoxide, [55] which have been effective methods in the planar chiral ferrocene literature. These studies have revealed some interesting results such as the ability to changet he overall diastereoselectivity of the reactiont hrough careful ligand choice (Scheme 12) and thus avoid the need to use both enantiomerso ft he chiral isopropyl oxazoline calix[4]arene 28.…”
Section: Meta-functionalisationmentioning
confidence: 99%
“…Relatively few mono‐substituted calix[4]arenes have been reported. This observation is all the more surprising when their versatility and critical use as components of electron‐switches, supramolecular calixpeptides, enzyme mimics, catalysts, molecular recognition, ESR probes, organocatalysts, and nucleoside motifs, and in procedures for asymmetric hydrogenation, and chiral lithiation, are taken into consideration. The explanation is that it is easier to fully substitute (i.e., tetrasubstitute) a calix[4]arene than it is to perform the reaction exclusively at just one of the four identical rings of the macrocycle.…”
Section: Introductionmentioning
confidence: 99%